TRANSNATIONAL BUSINESS IN VIEW OF NATIONAL ECONOMIC SECURITY (THEORETICAL ASPECTS) - N. H. Vafina (Стратегические решения и риск-менеджмент)
In view of the controversial nature of the transnational enterprise activity, it becomes relevant the development of monitoring mechanisms, system analysis, the control of processes of the production transnationalization from an economic security position. In the given article it is described the features of state influence on transnational business for national economic interests. It is identified the conditions for effective regulation of the processes of product transnationalization under the increasing of the economic instability.